2019
DOI: 10.1177/1753495x18807549
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic profile in the second and third trimesters of normal pregnancy compared to non-pregnant adult females

Abstract: Aim To assess the glycaemic profile and glycaemic variation in the second and third trimesters of normal pregnancies. Methodology Healthy pregnant women aged 19–35 years between 24 and 36 weeks of gestation were recruited for ambulatory glucose profile monitoring. A total of 18 women in the second trimester, 15 women in the third trimester and 9 healthy non-pregnant women were recruited providing, respectively, 205 days (19,680 data points), 147 days (14,112 data points) and 100 days (9,600 data points) for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…This report agrees with that of Nigam et al which revealed a significant decrease in blood glucose levels in women who were in their second and third trimesters of pregnancy compared to that of the non-pregnant women; this may be so because the dynamics of glucose during pregnancy is altered and physiologic adaptation occurs throughout gestation to ensure adequate transfer of glucose to the fetus for proper development. 8 However, the report obtained from this study disagrees with that of Nwaoguikpe and Uwakwe which stated a rise in plasma glucose concentration as the gestational period increased, and this may be attributed to the presence of gestational diabetes (induced by some placental hormones) in the pregnant women they used in their study. 9 Also, the results reveal that the plasma chromium concentration increased significantly in the third trimester of the pregnancy.…”
Section: Discussioncontrasting
confidence: 89%
“…This report agrees with that of Nigam et al which revealed a significant decrease in blood glucose levels in women who were in their second and third trimesters of pregnancy compared to that of the non-pregnant women; this may be so because the dynamics of glucose during pregnancy is altered and physiologic adaptation occurs throughout gestation to ensure adequate transfer of glucose to the fetus for proper development. 8 However, the report obtained from this study disagrees with that of Nwaoguikpe and Uwakwe which stated a rise in plasma glucose concentration as the gestational period increased, and this may be attributed to the presence of gestational diabetes (induced by some placental hormones) in the pregnant women they used in their study. 9 Also, the results reveal that the plasma chromium concentration increased significantly in the third trimester of the pregnancy.…”
Section: Discussioncontrasting
confidence: 89%
“…The daily pattern and glucose pattern reports were downloaded using the Freestyle Libre Pro Software for desktop (Abbott). Flash glucose sensors have been previously used with pregnant populations to assess glycemic profile and glycemic variation during the second and third trimesters of nondiabetic individuals (Nigam et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…To understand these results, one needs to keep in mind that the mechanisms driving insulin resistance in a healthy pregnancy, as well as in a pregnancy complicated by hyperglycemia, are complex and differ from the non-pregnant scenario. [ 26 ] Cousins et al have performed a longitudinal study to quantify the progressive effects of the second and third trimesters of normal pregnancy on the levels of plasma glucose and insulin and to compare it with non-pregnant controls. During pregnancy, the peak anabolic values for both plasma glucose and insulin were significantly increased and consequently, the 2-hour postprandial glucose and insulin levels were significantly elevated after meal ingestion and higher compared to non-pregnant controls.…”
Section: Discussionmentioning
confidence: 99%